Tinjauan Yuridis Pasal 75 Undang-Undang Keimigrasian Terhadap Pengawasan Orang Asing Dalam Ekosistem Ekonomi Digital Indonesia - I Gede Prama Dutha Eswara; I Made Rico Dvipayana; Faizh Ramadhani (Jurnal Ilmiah Penegakan Hukum, 2026)
This study aims to determine and analyze the immigration oversight system, which still relies on Article 75 of Law Number 6 of 2011, which contains multi-interpretable phrases such as "dangerous activities" and "reasonably suspected of disturbing public order," thus potentially creating legal uncertainty in the discretionary practices of immigration officials. The research method uses normative juridical research that analyzes the normative construction of Article 75 and related regulations, including Law Number 27 of 2022 concerning Personal Data Protection and Government Regulation Number 40 of 2023, to examine the harmony of norms and the fulfillment of the principle of legal certainty in monitoring the digital activities of foreigners. The results of the study indicate a dilemma between the need to uphold sovereignty through Immigration Administrative Actions and efforts to maintain the investment climate and Indonesia's attractiveness as a digital economic hub, caused by the lack of measurable operational parameters and clear limits on digital oversight authority. This condition expands the discretionary space for immigration officials and has the potential to lead to inconsistencies in the application of the law. This study also confirms the potential conflict between immigration oversight and the principle of personal data protection. Therefore, the study recommends the creation of a ministerial regulation that specifically classifies administrative violations by foreign digital workers, formulates indicators of "dangerous activities" based on online activities, and integrates personal data protection into the design of adaptive and proportional immigration oversight in the digital era.